Immunohistochemical expression of p53 and Fox A1 in epithelial ovarian cancer - Elnashar, Afaf T; Youssef, Esraa M (Clinical Journal of Obstetrics and Gynecology, 2022)
Background: Ovarian cancer (OC) is the fifth cause of cancer mortality in females. There were an estimated 300,000 new cases of OC diagnosed worldwide in 2018, corresponding to 3.4% of all cancer cases among women. The high mortality rate of OC attributed to asymptomatic growth of the tumor leads to its diagnosis at advanced stages. About 85% - 90% of OC are epithelial including serous, endometrioid, clear cell, and mucinous carcinoma. Aim: To study the immunohistochemical (IHC) expression of FOX A1 and p53 in epithelial OC and its association with prognostic indicators such as age, tumor size, stage, grade, and histological type. Materials and methods: The study included 52 cases with EOC from the pathology department, faculty of medicine, Aswan, and Sohag Universities, in the period from January 2017 to December 2019. This study involved 52 patients with OC and a median age of 53 years. Different histological types were included as 37 serous, 12 mucinous, 1 case endometroid 2 cases clear cell OC. The study cases were classified into 22 Grade I, 16 Grade II, and 20 Grade III. About 22 cases were at stage I, 9 at stage II, 11 at stage III, and 10 at stage IV. Tissue sections were stained using the IHC technique with FOX A1 at a dilution of 1:100 and p53 at 1:100. Results: A statistically significant correlation was found between FOX A1 expression and advanced patient’s age, high grade, advanced stage, ruptured capsule, and ascites, regardless of tumor laterality. No significant association was found between p53 immunoexpression and the same clinic-pathological parameters although p53 was associated with serious type. Conclusion: FOX A1 immunoexpression in EOC is considered a poor prognostic factor in EOC. FOX A1 could be a potential therapeutic target and prognostic marker in EOC.